The impact of postmenopause on sleep and sleep disorders: The current state of the art (Research, Society and Development, 2023)
Sleep disorders in postmenopausal women are important symptoms that demonstrate the impact of the hormonal changes that have begun since menopause. Hormonal changes during the transition to postmenopause play a crucial role in sleep disorders, contributing to symptoms such as insomnia, hot flashes, obstructive sleep apnea and restless legs syndrome. Such disorders impact on women's quality of life, increasing the risks of developing chronic and psychological health conditions, including depression, anxiety and cardiovascular disease. In addition, Hormone Replacement Therapy (HRT) in the treatment of menopausal symptoms is the most widely used pharmacological therapy, although its effectiveness in improving sleep quality is still uncertain due to the heterogeneous nature of the results. Sleep hygiene, together with Cognitive-Behavioral Therapy for Insomnia (CBT), has emerged as a promising non-pharmacological approach to the management of sleep disorders in postmenopausal women. The management of sleep disorders in postmenopausal women should be analyzed taking into account the physical, psychological and hormonal aspects of the patients.